Novel Lipid Formulation Increases Absorption of Oral Cannabidiol (CBD) - Edward Chesney; Ndabezinhle Mazibuko; Dominic Oliver; Amedeo Minichino; Ayşe Doğa Lamper; Lucy Chester; Thomas J. Reilly; Millie Lloyd; Matilda Kråkström; Alex M. Dickens; Matej Orešič; Eric Lynch; et al. (Pharmaceutics)
Background: Cannabidiol (CBD) is an approved treatment for childhood epilepsies and a candidate treatment for several other CNS disorders. However, it has poor oral bioavailability. We investigated the effect of a novel lipid formulation on its absorption in humans and on its tissue distribution in mice. Methods: In a double-blind crossover study in fasting healthy volunteers, we compared the pharmacokinetics of a single dose of 1000 mg of CBD in the lipid formulation and in a powder formulation (ClinicalTrials.gov: NCT05032807). In a second study, male CD1 mice were administered CBD in either the lipid formulation or dissolved in water, via oral gavage (n = 1 per timepoint). The tissue distribution of CBD was assessed using matrix-assisted laser desorption/ionization mass spectrometric imaging. Results: Plasma exposure (AUC0–48) of CBD was nine times greater for the lipid formulation than the powder formulation (611.1 ng·h/mL [coefficient of variation CV%: 104.6] and 66.8 ng·h/mL [CV%: 50.7], respectively). With the powder formulation, the AUC0–48 was related to the concentration of specific gastrointestinal bacteria and bile acids. These associations were attenuated with the lipid formulation. In the animal study, after treatment with the lipid formulation, measurable concentrations of CBD were identified in all organs. For the aqueous formulation, tissue concentrations of CBD were below the limit of quantification. Conclusions: Administering oral CBD in a lipid formulation was associated with an increase in its gastrointestinal absorption, as well as an attenuation of the relationship between its absorption and features of the gut microbiome.